2006
DOI: 10.1158/1055-9965.epi-06-0072
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in Metabolic Genes Related to Tobacco Smoke and the Risk of Gastric Cancer in the European Prospective Investigation into Cancer and Nutrition

Abstract: Metabolizing enzymes, which often display genetic polymorphisms, are involved in the activation of compounds present in tobacco smoke that may be relevant to gastric carcinogenesis. We report the results of a study looking at the association between risk of gastric adenocarcinoma and polymorphisms in genes CYP1A1, CYP1A2, EPHX1, and GSTT1. A nested case-control study was carried out within the European Prospective Investigation into Cancer and Nutrition, developed in 10 European countries. The study includes 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 35 publications
(36 reference statements)
2
35
0
Order By: Relevance
“…Another study at our institute had also shown no association between CYP1A1 gene polymorphism and esophageal cancer [37]. The large EPIC-EURGAST case-control study also supported these findings for polymorphism of CYP1A1 [38]. In the case of the CYP1A2 gene, -164A to C substitution leads to a decrease in enzyme activity [22].…”
Section: Discussionsupporting
confidence: 58%
“…Another study at our institute had also shown no association between CYP1A1 gene polymorphism and esophageal cancer [37]. The large EPIC-EURGAST case-control study also supported these findings for polymorphism of CYP1A1 [38]. In the case of the CYP1A2 gene, -164A to C substitution leads to a decrease in enzyme activity [22].…”
Section: Discussionsupporting
confidence: 58%
“…Some studies investigated gene interaction with tobacco smoking in gastric cancerogenesis. Polymorphisms of GSTT1, SULT1A1, CYP1a1, and NAT2 genes appear to be implicated in modulating individual susceptibility in the relation between smoking and gastric cancer (Agudo et al, 2006;Lee et al, 2006;Boccia et al, 2007). Furthermore, the hypermethylation of the CDH1 gene was observed preferentially in gastric tumors from smokers rather than nonsmokers (Poplawski et al, 2008).…”
Section: Pooled Estimatementioning
confidence: 99%
“…DNA samples from 243 gastric cancer cases and 946 matched controls, selected from the European Prospective Investigation into Cancer and nutrition (EPIC) cohort according to a nested case-control design, 13 were used to analyze the GSTT1 and GSTM1 null polymorphisms by real-time PCR and melting curve analysis in a LightCycler 2.0 (LC2.0). DNAs were extracted with the Puregene DNA Purification System (Gentra Systems, Minneapolis, MN) adapted to the Gentra Autopure LS DNA preparation platform (Gentra Systems) and dried for storage.…”
Section: Dna Samplesmentioning
confidence: 99%
“…Before use, DNAs were reconstituted with water. 13 Moreover, samples of 792 subjects (cases and controls) from this study were reanalyzed by conventional multiplex PCR and gel electrophoresis. A group of 300 DNA samples from healthy subjects selected from the EPIC Spain cohort 14 were used to validate the assay for performance in the LightCycler 480 (LC480).…”
Section: Dna Samplesmentioning
confidence: 99%